2024
DOI: 10.3389/fpls.2024.1343222
|View full text |Cite
|
Sign up to set email alerts
|

Bulbil initiation: a comprehensive review on resources, development, and utilisation, with emphasis on molecular mechanisms, advanced technologies, and future prospects

Fuxing Shu,
Dongdong Wang,
Surendra Sarsaiya
et al.

Abstract: Bulbil is an important asexual reproductive structure of bulbil plants. It mainly grows in leaf axils, leaf forks, tubers and the upper and near ground ends of flower stems of plants. They play a significant role in the reproduction of numerous herbaceous plant species by serving as agents of plant propagation, energy reserves, and survival mechanisms in adverse environmental conditions. Despite extensive research on bulbil-plants regarding their resources, development mechanisms, and utilisation, a comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 150 publications
0
5
0
Order By: Relevance
“…Different plants exhibit varying developmental pathways for their bulbils. For example, bulbils morphologically progress from a ‘torpedo shape’ to an ‘embryo shape’ and finally to a ‘spherical shape’ during their development in the Lilium lancifolium [ 7 ]. We found that a P. ternata bulbil emerges from a white punctate structure, which subsequently undergoes both longitudinal elongation and lateral expansion, ultimately developing into an oval spherical configuration.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Different plants exhibit varying developmental pathways for their bulbils. For example, bulbils morphologically progress from a ‘torpedo shape’ to an ‘embryo shape’ and finally to a ‘spherical shape’ during their development in the Lilium lancifolium [ 7 ]. We found that a P. ternata bulbil emerges from a white punctate structure, which subsequently undergoes both longitudinal elongation and lateral expansion, ultimately developing into an oval spherical configuration.…”
Section: Discussionmentioning
confidence: 99%
“…Phytohormones, also known as plant hormones or growth regulators, regulate various processes in plant growth, development, and environmental adaptation at extremely low concentrations [ 7 ]. These processes work independently yet cooperatively to collectively regulate nutritional growth, reproductive growth, seed germination, seed maturation dormancy, embryo development, and adaptation to biotic and abiotic stresses [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations